Concept Creep and Psychiatrization - Haslam, Nick; Tse, Jesse S. Y.; De Deyne, Simon (Frontiers in Sociology, 2021)
Some aspects of psychiatrization can be understood as forms of concept creep, the progressive expansion of concepts of harm. This article compares the two concepts and explores how concept creep sheds light on psychiatrization. We argue that although psychiatrization is in some respects a broader concept than concept creep, addressing institutional and societal dimensions of the expanding reach of psychiatry in addition to conceptual change, concept creep is broader in other respects, viewing the expansion of psychiatric concepts as examples of the broadening of a more extensive range of harm-related concepts. A concept creep perspective on psychiatrization clarifies the different forms of expansion it involves, the centrality of harm to it, its benefits as well as its costs, its variations across individuals and groups, and the drivers of psychiatrization in the general public and in fields beyond psychiatry.